2008
DOI: 10.1118/1.2940157
|View full text |Cite
|
Sign up to set email alerts
|

Dose distribution of a 125 keV mean energy microplanar x-ray beam for basic studies on microbeam radiotherapy

Abstract: A multislit collimator was designed and fabricated for basic studies on microbeam radiation therapy (MRT) with an x-ray energy of about 100 keV. It consists of 30 slits that are 25 microm high, 30 mm wide, and 5 mm thick in the beam direction. The slits were made of 25 microm-thick polyimide sheets that were separated by 175 microm-thick tungsten sheets. The authors measured the dose distribution of a single microbeam with a mean energy of 125 keV by a scanning slit method using a phosphor coupled to a charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…The nominal beam width was 25 mm (industrial-grade kapton sheets). Ohno et al [23] reported the effective beam width for this collimator at full width half maximum was 21.2-23.1 mm with a centre-to-centre spacing of exactly 200 mm. The peakto-valley dose ratio for this collimator was measured using radiochromic films of different sensitivity.…”
Section: Synchrotron Radiation Source and Microbeam Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…The nominal beam width was 25 mm (industrial-grade kapton sheets). Ohno et al [23] reported the effective beam width for this collimator at full width half maximum was 21.2-23.1 mm with a centre-to-centre spacing of exactly 200 mm. The peakto-valley dose ratio for this collimator was measured using radiochromic films of different sensitivity.…”
Section: Synchrotron Radiation Source and Microbeam Generationmentioning
confidence: 99%
“…The synchrotron X-ray beam was filtered by passing through a 3 mm-thick copper absorber that preferentially absorbs low energy X-rays and hence increases the beam's mean energy. The mean energy of the filtered X-ray beam was 125 keV [23]. A tungsten/ kapton collimator segmented the BB into a lattice of planar microbeams.…”
Section: Synchrotron Radiation Source and Microbeam Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Each microbeam is approximately 25-μm wide with a spacing of 200 μm between adjacent microbeams. The details of the beams and multislit irradiation system have been described by Kashino et al [9], Ohno et al [16] and Nariyama et al [17]. The cells were then fixed with 4% paraformaldehyde in phosphate buffer saline immediately after irradiation and at 6, 12 and 24 h after irradiation.…”
Section: Cell Irradiation With Microplanar Beam At Spring-8mentioning
confidence: 99%
“…14,15 The ultra-high dose rates (>100 Gy/s) allow for the instantaneous delivery of the high dose in tens of milliseconds, thus maintaining the microbeam profile despite the physiological motion which is on the order of hundreds of micrometers and the time scale of 100 s of milliseconds. Another reason that so far the method could not be implemented with sources other than synchrotron is that the near parallel beam and high dose rate make it easier to collimate the beam into parallel microplanar beams.…”
Section: A Microbeam Radiation Therapy (Mrt)mentioning
confidence: 99%